(untitled) (Altre Modernità, 2024)
In Steve Yockey’s Octopus (2008), a ravenous sea monster embodies AIDS. A cheerful telegram delivery boy, a drenched messenger on an otherwise sunny day, delivers the news of contagion. The patient is a quick-witted gay man whose emotions are out of sync with his partner’s long before group sex enters the equation. The play is a health tragedy centered on collective trauma and individual illness, in which AIDS is explored through the conventions of the horror genre because of the overlapping representational codes. In Octopus, no distinction is made between good gays and bad queers: the characters are people with their fair share of flaws and virtues. Thus, without stigmatizing, dehumanizing, or overly sanitizing the lives of gay men—at the risk of making the story unpalatable to the audience, Yockey proves theatre’s aptness to portray illnesses and patients, painting the latter as people rather than a set of symptoms. Following this, this paper aims to analyze Octopus through the lens of medical humanities, focusing on the deconstruction of the fragility of communal and private relationships and the potentiality of hope in the face of an epidemic.